PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP PENURUNAN DISMENOREA PADA REMAJA PUTRI - Vivin Dewi Safutri; Ayudita (Institut Citra Internasional, 2026)
Menstrual pain is typically felt in the lower abdomen and may radiate to the back, thighs, groin, and vulva. This condition may also be accompanied by nausea, diarrhea, and dizziness. During menstruation, adolescent girls often experience fear and negative thoughts, which can intensify the perceived pain. SEFT therapy can be used as a non-pharmacological method to manage pain by combining tapping techniques on specific body points with spiritual elements and the body’s energy system. The purpose of this study was to determine the effect of SEFT therapy on menstrual pain among adolescent girls in Mancung Village, Kelapa District, West Bangka Regency in 2025.This research employed a quasi-experimental method with a Pretest–Posttest Control Group Design, involving two groups: an experimental group and a control group. The experimental group consisted of 18 respondents who received SEFT therapy, while the control group included 18 respondents who did not receive the therapy. The sampling technique used was purposive sampling, in which participants were selected based on specific criteria relevant to the study.Based on the results, SEFT therapy had a significant effect on reducing menstrual pain (p-value = 0.002) among adolescent girls in Mancung Village, Kelapa District, West Bangka Regency in 2025. It is recommended that adolescent girls apply SEFT therapy before menstruation and especially when experiencing menstrual pain as a non-pharmacological method that is safe and free from side effects.